Uma pequena cidade capixaba : desafios frente à urbanização e a industrialização em Santa Maria de Jetibá/ES - Potratz, Raphael Henrique Ferreira (2019)
Faced with the phenomenon of industrialization and rapid urbanization that has developed since the 1950s in the large and medium-sized cities of Brazil, and with its own characteristics in Espírito Santo, this research aims to identify and situate the imp